2003
DOI: 10.2202/1554-8597.1058
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Peace on Regional Economic Cooperation in the Middle East

Abstract: The peace process in the Middle East has heightened the prospects of potential benefits from regional economic cooperation. However, its actual implementation is subject to many constraints, stemming from the economic gaps between the countries, significant differences in social and economic structures and the prevalence of other non-economic priorities. Patterns of economic cooperation in specific fields (projects, trade, labor and capital) are identified and analyzed in terms of their sensitivity to constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Hazboun and Bahiri (1994) found that joint ventures are the favored form of cooperation of 71 percent of Israeli firms and 56 percent of Palestinian firms. Bar-El and Schwartz (2003) analyzed the benefits of regional cooperation in the Middle East and categorized them into three categories: economies of scale, complementarities between production factors, and externalities. Bar-El and Malul (2008) considered two types of externalities-those defined as macroeconomic and those defined as sociopolitical.…”
Section: Introductionmentioning
confidence: 99%
“…Hazboun and Bahiri (1994) found that joint ventures are the favored form of cooperation of 71 percent of Israeli firms and 56 percent of Palestinian firms. Bar-El and Schwartz (2003) analyzed the benefits of regional cooperation in the Middle East and categorized them into three categories: economies of scale, complementarities between production factors, and externalities. Bar-El and Malul (2008) considered two types of externalities-those defined as macroeconomic and those defined as sociopolitical.…”
Section: Introductionmentioning
confidence: 99%